The Relationship Between Stress Levels And The Incidence Of Dysmenorrhea In Adolescent Females At State Middle School 4 Banyuwangi - Nur Hidayati; Saptaningsih, Heni (Jurnal Ilmu-Ilmu Kesehatan, 2025)
Stress is one factor that can cause dysmenorrhea, a menstrual disorder. Stress can increase the production of prostaglandin hormones, which can stimulate uterine muscle contractions, resulting in pain. The purpose of this study was to determine the relationship between stress levels and the incidence of dysmenorrhea in female students at SMP Negeri 4 Banyuwangi. The research method was descriptive correlational using a cross-sectional approach with a purposive sampling technique and 72 respondents. Key findings showed that among adolescents, 26.4% had mild stress, 26.4% moderate stress, 23.6% normal stress, 16.7% severe stress, and 6.9% very severe stress. Regarding dysmenorrhea, 48.6% reported moderate pain, 29.2% mild pain, 18.1% severe pain, and 4.2% unbearable pain. There was a statistically significant correlation between stress levels and dysmenorrhea incidence (t-test, p=0.000, correlation coefficient 0.74), indicating that higher stress is associated with higher intensity of dysmenorrhea. Further research is recommended to include other variables such as age at menarche and family history.